Edukasi Senam Kaki terhadap Kemampuan Melakukan Senam Kaki pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Kereng Bangkirai Palangka Raya - Yuyun Christyanni; Novi Mery Kala Aheng; Yongwan Nyamin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The incidence of diabetes mellitus shows an increasing prevalence today. This condition is influenced by the lack of knowledge of clients in the management of Diabetes Mellitus. Efforts to increase knowledge can be done through education using media and effective methods. The use of audiovisual media is believed to be the most effective media in conveying information. Education in this study used audiovisual media that was applied in conjunction with the demonstration method. The purpose of this study was to analyze the effect of education with audiovisual media and demonstration methods on the ability to do foot exercises in patients with Type 2 Diabetes Mellitus in the work area of KerengBangkirai Health Center, Palangka Raya. The research method used was a quasy experiment with one group pre and post-test design. The sampling technique was done by purposive sampling as many as 30 peoples. The results showed that there were differences in knowledge and ability to do foot exercise before and after the education which was shown from the results of the paired t-test obtained p-value = 0,000 <α = 0.05. Foot exercise education with audiovisual media and demonstrations had an effect on the ability to do foot exercise in patients with Type 2 Diabetes Mellitus in the working area of Kereng Bangkirai Health Center.